1995
DOI: 10.1002/gcc.2870130211
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a t(I0; II) (pI3‐I4; qI4‐2I) in the monoblastic cell line U937

Abstract: Previous analysis of the monoblastic cell line U937 has shown that several sublines contain a rearranged chromosome arm 11q. In order to determine the true nature of the rearrangement, fluorescence in situ hybridization (FISH) was carried out with various combinations of single copy anonymous markers, clones containing genes, a chromosome 10 paint, and an 11 centromere specific sequence. The rearrangement was deduced to be a reciprocal translocation between chromosomes 10 and 11 described as t(10;11)(p13-14;q1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 28 publications
(34 reference statements)
1
10
0
Order By: Relevance
“…However, two YACs that contained BMII (815c7 and 936g7) clearly mapped proximal to the translocation breakpoint. This observation is consistent with the results of Shipley et al (3) who used a phage insert containing the BMII gene for FISH analysis in U937. Fig.…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…However, two YACs that contained BMII (815c7 and 936g7) clearly mapped proximal to the translocation breakpoint. This observation is consistent with the results of Shipley et al (3) who used a phage insert containing the BMII gene for FISH analysis in U937. Fig.…”
Section: Resultssupporting
confidence: 83%
“…Its karyotype is complex and the true identity of many rearrangements has not yet been resolved. We and others have shown by fluorescence in situ hybridization (FISH) that one of these rearrangements is a reciprocal (10;11)(p13;q14) translocation (3,4). We now report that this translocation leads to the fusion of AFIO at 1Opl3 to a novel gene, CALM, at 11q14.…”
mentioning
confidence: 79%
See 2 more Smart Citations
“…9 The presence of a reciprocal translocation between chromosomes 10 and 11, a t(10;11)(p13-14; q14-21) in the U937 cell line was confirmed and subsequently refined by cytogenetic analysis. 10,11 Using positional cloning techniques to narrow the chromosome 10 breakpoint to a 3 cM region, AF10 was identified as a candidate gene on chromosome 10 potentially involved in this translocation. Subsequent studies showed that the AF10 gene was indeed disrupted by the t(10;11) translocation, and identified CALM as the AF10 fusion partner in this recurrent translocation.…”
Section: Introductionmentioning
confidence: 99%